Transduction of proto-src sequences in tissue culture by a molecular clone of transformation-defective Rous sarcoma virus with an internal src deletion. - Phares, W (1988)
The sporadic appearance of nondefective (nd) Rous sarcoma virus (RSV) from cells in tissue culture infected with a molecular clone of transformation-defective RSV was examined. Southern analysis of extrachromosomal, virus-specific DNA of three independent ndRSV isolates in each case indicated restoration of an isogenic src by homologous recombination with cellular proto-src. The frequency of transduction was estimated by fluctuation analysis to vary between one transduction per 0.4 x 10(7) to 1.6 x 10(7) infected cells.